FAKTOR-FAKTOR YANG MEMENGARUHI IBU DALAM PEMBERIAN MAKANAN PENDAMPING ASI TERLALU DINI DI WILAYAH KERJA UPTD PUSKESMAS TELUK KARANG KECAMATAN BAJENIS KOTA TEBINGTINGGI PROVINSI SUMATERA UTARA TAHUN 2015 - novianti damanik; Erna Mutiara; Maya Fitria (Gizi, Kesehatan Reproduksi dan Epidemiologi, 2016)
ABSTRACT The early complementary feeding is foods or drinks that contain nutrients given to infants under 6 months of age. The early complementary feeding at this time will reduce the coverage of exclusive breastfeeding. The coverage of exclusive breastfeeding in the Puskesmas Teluk Karang was still low about 32,8% (in 2014) while the national target was 80%. It is suspected related to factors of social culture and family support. The purpose of this study was to understand factors influenced the mothers in giving the early complementary feeding in working area of UPTD Puskesmas Teluk Karang, Subdistrict of Bajenis, City of Tebing Tinggi in 2015. Type of this research was analytical observation study with the cross sectional design. The research was done since November 2013 until January 2015. Population in this research were all mothers who had infant aged between 7-12 months in the working area of UPTD Puskesmas Teluk Karang, Subdistrict of Bajenis, City of Tebing Tinggi which was being as samples as 106 mothers. The multiple logistic regression is used to analyze the data. The result of the research showed that the early complementary feeding is high enough i.e 89,6%. From the multivariate analysis, it was proved that the factors influenced the early complementary feeding are the social culture (p=0,008) and the family support (p<0,001). The dominant factor influenced this early complementary feeding was family support (coefficient of B=3,021). It’s suggested that breastfeeding mothers are not easily influenced by the social culture in the communities and families are expected to provide support so that mothers still exclusively breastfed, by fulfilling the nutritional needs during lactation so that it produced the qualified breastfeeding in the sufficient quantities. Keywords: Early Complementary Feeding, Social Culture, Family Support